Computer simulation of annual work cycle of combined refrigeration system using night radiative cooling - A. P. Tsoy; A. V. Baranenko; A. S. Granovskiy; D. A. Tsoy; D. A. Koretskiy; R. A. Jamasheva (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Evaluation of energy efficiency of a combined cooling system that uses night radiative cooling together with refrigerating machine with accumulation of cold without a phase transition and the supply of liquid coolant (propylene glycol) to the air cooler is performed based on the results of computer simulation. In the cooling system located in Kostanay (Kazakhstan), there are radiators (12 m2) that cool the coolant at night, as well as a conventional vapor compression refrigerating machine with a reciprocating compressor. The cooling system is used to maintain air temperature at the level of 0±1°C in a small refrigeration chamber (36 m3) with a low value of heat emission from stored products and the absence of other operational heat influx. It is found that 78,8 days a year the cooling system can maintain the required temperature due to the operation of radiators without turning on the refrigerating machine. This saves 242 kWh of electricity. Thus, the combined refrigeration system provides 7,6% reduced energy consumption, and also reduces physical deterioration of the refrigerating machine compressor for the annual cycle, which should reduce the financial costs for operating the refrigeration warehouse